INFLUENCE OF DIFFERENTLY DIRECTED MOTOR ACTIVITY ON INDICATORS OF EXTERNAL RESPIRATORY FUNCTIONS IN THE PROCESS OF SPECIAL PHYSICAL TRAINING IN BOXING - Neupokoev, S.N.; Bredikhina, Yu.P.; Shilko, V.G.; Guseva, N.L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the influence of multidirectional muscle activity on the functional parameters of the external respiration apparatus during the performance of special physical training exercises in boxing. Methods and structure of the study. Two equivalent groups were formed from boxers of the 1st category from 18 to 19 years old, 10 people in each group: the experimental group (EG) and the control group (CG). All athletes were represented by the weight category up to 71 kg. Within six months, the athletes were tasked with improving special physical training based on the tactical features of the fight. Boxers who use a playful style of fighting and achieve sports results by winning by beating an opponent on points (boxers-players) used means aimed at a more significant development of the muscles of the lower extremities when performing punches (EG). Athletes who use a strong blow to achieve the result (boxers-knockouts) performed exercises with a more significant involvement of the muscles of the upper limb girdle (CG) in the activity. Results and conclusions. It has been noted that the use of agents that involve the muscles of the lower extremities in the activity contributes to the development of optimal functional training in boxing, which qualitatively affects the spirographic parameters after the performed motor work of athletes.